Faktor-Faktor yang Mempengaruhi Kejadian Stunting pada Anak: Studi Literatur - Slamet Ali Mashar; Suhartono Suhartono; Budiono Budiono (Jurnal Serambi Engineering, 2021)
Stunting is a global health problem  and in Indonesia, both in urban and rural areas. Stunting occurs in children and if preventive actions  are not taken such as nutrition, immunization, and maintain a clean environment, it may  cause disturbances in children  in brain development, body metabolism, and physical growth. Risk factors for stunting in children’s  parental habits , basic immunization, basic sanitation, history of infectious diseases, smoking habits, and upper respiratory tract infections. The purpose of this study is to provide information on  factors that play a role  in the  risk of stunting according to  a review study. This study uses a descriptive method with a literature review approach using previous research from  the Sinta database. The review  criteria used are indexed by Sinta 2, 3, 4, and 5, published  times over the last 5 years. The conclusion  of  this literature review study is that there are several factors associated with  the incidence of stunting such as the parenting habits  of children, basic immunization, basic sanitation, history of infectious diseases, smoking habits, and incidence of respiratory infections.